The adsorption characteristics of 2D fibril and 3D hydrogel aggregates at the O/W interface combining molecular dynamics simulation - Han, Zongyuan; Yue, Xiqing; Shao, Jun-Hua (Food hydrocolloids, 2022)
The 2D/3D microstructures and hydrophobic domains of interfacial proteins play important roles in interfacial adsorption and emulsification stability. The effects of spatial conformation, crystal structure and micro-structures on interfacial adsorption were investigated combining molecular dynamics simulation. The results showed that with the increase of pHs, the α-helix contents and surface hydrophobicity in the emulsified aggregates decreased significantly, and the β-sheet contents increased significantly, in which the formation of interfacial protein membrane caused molecular re-arrangement. The α-helix contents and surface hydrophobicity in 2D fibril aggregates were significantly higher than those in 3D hydrogel aggregates, but the β-sheet result was opposite along with different hydrophobic amino acid sequences. The peak intensity and crystallinity of interfacial proteins in hydrogel aggregation mode were higher than those in fibril aggregation mode, and the transformation of crystal structure can affect the interfacial microstructure. The interfacial protein membrane is mainly composed of fibrous rod-like aggregates, among which 2D fibrous network structure is formed at pH 3.0 and 3D multilayer network structure is formed at pH 9.0. Due to the differences in spatial conformation, crystal structure and characteristic micro-structure caused by emulsification and adsorption, the interfacial adsorption rate of 2D fibril aggregates is higher, and the ability of 3D hydrogel aggregates to reduce interfacial tension is greater. [Display omitted] •The adsorption rate of fibril aggregates is higher, and the interfacial tension of hydrogel aggregates is lower.•Hydrophobic amino acid sequences of 2D/3D aggregates mainly affected the stability of the interfacial membrane.•The main force of 2D/3D aggregates at the interface was hydrophobic force and hydrogen bond, respectively.•Crystal structure and spatial structure could influence interfacial adsorption and viscoelastic characteristics.•2D/3D microstructure of interfacial protein membrane can determine interfacial adsorption and emulsification stability.